MEMOTRET KEBERHASILAN SIMRS TERHADAP KUALITAS PELAYANAN SELAMA PANDEMI COVID-19 DI RUMAH SAKIT SWASTA DI BALI - Widyantari, Ni Luh Komang Try; Prianthara, Ida Bagus Teddy (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.10.NO.08.TAHUN.2021, 2021)
This study aims to capture HIS achievement on the quality of service during the Covid-19 pandemic in private hospitals in Bali. This research has been conducted at a private hospital in Bali that has and implements HIS, by giving questionnaires to 100 respondents. The research data were analyzed using the SEM (Structural Equation Model) method using SmartPLS 3.3. The results of this study were Safety Quality, System Quality, and Information Quality from the HIS proved to have a positive and significant effect on the quality of health services during the Covid-19 pandemic in private hospitals in Bali (t-statistic > 1,96 and p-value < 0,05). Service Quality from HIS has not been proven to have a positive and significant effect on the quality of health services during the Covid-19 pandemic in private hospitals in Bali (t-statistic < 1,96 and p-value > 0,05). The quality system of the HIS is the most dominant factor affecting the quality of health services which has a path coefficient of 0.526